PENGARUH MEDIA AUDIO DAN AUDIO VISUAL TERHADAP KEMAMPUAN MENYIMAK SISWA KELAS IV SEKOLAH DASAR - Dominsius Dito Pratama (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Listening skill is the most fundamental skill that students must possess. The low listening skills of fourth-grade students at SD Kanisius Cungkup Salatiga and SD Negeri Kutowinangun 08 Salatiga in the subject of fairy tales, coupled with inadequate use of media, constitute the background of this research. The aim of this study was to determine the difference in the effects of audio and audio-visual media on elementary school students' listening skills. This research employed a quasi-experimental design using a nonequivalent control group design. The results indicated that the use of audio and audio-visual media has an influence on the listening skills of fourth-grade students at SD. This is evident from the average scores of the experimental and control groups. With a obtained (2-tailed) p-value of 0.029 < 0.05, H0 was rejected and Ha was accepted. Thus, it can be concluded that audio and audio-visual media have an impact on the listening skills of fourth-grade students elementary school.